PENGGUNAAN METODE EKSPERIMEN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA POKOK BAHASAN PENGHANTAR PANAS PADA SISWA KELAS VI SDN 1 DAWUAN KECAMATAN SUBOH KABUPATEN SITUBONDO TAHUN PELAJARAN 2012/2013 - Sri Wahyuni; Amalia Risqi Puspitaningtyas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2013)
In performing the duties of elementary classroom teachers still see a lot of different problems, including a lot of discussion of any subject that is not fully controlled by the student in accordance with the standards of competence expected. Faced not only the quality of the students, but related components in general as one of the educational institutions. Curriculum that is always changing and improving as an obstacle for teachers in the implementation of learning. From the preliminary observations in SDN 1 Interchange Sub Tampora Situbondo in sixth grade, especially in science learning, it can be concluded that teachers are more focused on classical and conventional approach without active approach, innovative, creative, efficient and enjoyable so that students do not actively participate in learning. The results obtained in this study indicate the percentage of students in the classical style in the first cycle, which was 64%. While the percentage of activity in the second cycle was 80%. Student learning outcomes using the experimental method in the first cycle that students who experience learning as much as 72%. While students who have not achieved mastery learning as much as 28%. In the second cycle of learning outcomes of students who suffer from learning as much as 80%. While students who have not achieved mastery learning as much as 20%